Small-scale gas to liquid fuel synthesis - Kanellopoulos, N. K. (CRC Press, 2015)
Aimed at overcoming significant costs and technical barriers prohibitive to the extensive use of conventional gas-to-liquid (GTL) processes for the exploitation of small and/or isolated natural gas reservoirs, the next-generation GTL technologies presented in this text reduce the expenses associated with air fractioning and syngas production. Showcasing contributions from the partners of two cooperating European research projects, namely the OCMOL and NEXT-GTL.
Keywords: Synthesis gas.; Liquid fuels.; Natural gas.; Methane.; Synthetic fuels.; elektronické knihy; electronic books